Case Report: A case of post-viral inflammatory insomnia: observed sleep restoration associated with histamine-targeted interventions and implications for mast cell pathways - Meckes, Amanda Jill; Meckes, James William (Frontiers in Sleep, 2026)
BackgroundMast cell-mediated inflammation has been proposed as a potential contributor to neuroinflammatory insomnia and dysautonomia, but objective clinical documentation remains limited. Histamine and related immune mediators can disrupt circadian rhythm, arousal systems, and autonomic stability. Conventional pharmacological therapies for sleep restoration often fail to address these inflammatory mechanisms.Case presentationA previously healthy and active 74-year-old male presented with post-viral dysautonomia and severe, treatment-refractory insomnia accompanied by persistent sneezing and ocular irritation suggestive of histamine reactivity. Despite optimal CPAP use and multiple pharmacological trials for sleep disturbance (zolpidem, trazodone, gabapentin, diazepam, lemborexant), Oura Ring data demonstrated persistently low sleep scores, often in the 30–40 range, and minimal REM and deep sleep. Routine laboratory studies (CBC, CMP, thyroid, cortisol, testosterone) were normal except for mildly low DHEA-S, consistent with chronic inflammatory stress. Following evaluation by a tertiary sleep specialist who suggested daytime stimulant therapy (declined by the patient), a targeted supportive regimen was initiated to promote physiologic recovery and restore sleep architecture. This included phosphatidylcholine, alpha-GPC, coenzyme Q10, cyproheptadine (2–4 mg at qHS) and removal of scented household products. Sleep metrics improved within 24 h, with Oura sleep scores increasing to 75+ from a 10-month period characterized by nightly scores often in the 30–40 range and remained stable thereafter. At 4-week follow-up, lingering daytime fatigue and patient-reported cognitive fog prompted additional dietary modification to a low-histamine pattern and the addition of loratadine (10 mg AM) and famotidine (20 mg BID).OutcomeWithin several days, the patient reported marked improvement in energy, cognition, and overall functional capacity, following nearly a year of functional incapacitation.ConclusionThis case demonstrates a reversible form of inflammatory insomnia and fatigue, likely mediated by mast cell-driven histamine activity. A multi-component intervention targeting histamine pathways, including antihistamine therapy, environmental modification, and dietary adjustment, was associated with rapid and sustained normalization of objective sleep metrics in this patient. These findings highlight the importance of evaluating immune and inflammatory contributors in patients with refractory insomnia and support further investigation of mast cell-related pathways in translational sleep medicine.